Exploring resistance factors on the usage of hospital information systems from the perspective of the Markus’s Model and the Technology Acceptance Model - Çiğdem Sıcakyüz; Oya Hacire Yüregir (Journal of Entrepreneurship, Management and Innovation)
Although information systems provide many benefits to the organization, many organizations are experiencing difficulties with the process of change. Resistance to change is one of the most considerable challenges in this phase. This study aimed to investigate the causes of resistance by healthcare personnel to IT in Adana Numune Hastanesi, which is a state-run hospital located in Adana, Turkey. The Technology Acceptance Model (TAM) was expanded by adding factors such as affective commitment, gender, and age. Logistic regression analysis was carried out on the research model through 291 collected survey data using SPSS (version 21). The overall percentage accuracy prediction was 55.3% for parameters of the initial model and 80.8% for the stepwise model after the third step. According to the results, while the factors “perceived usefulness of IT,” “perceived ease of use of IT,” and “affective commitment” were found to have an influence on the resistance of use of IT, demographic factors such as age, gender, position, and tenure were not related. Managers should create an environment for increasing staff commitment by including them in decision-making and process changing. Thus, not only could the manager use the organizations’ resources productively, but also future change projects could be carried out effectively, roughly, and timely. Therefore, through its committed personnel, the hospital could sustainably compete with its competitors in the market and make more profit.